Allo-HCT with post-transplant cyclophosphamide in older adults: similar safety and a viable option compared to younger adults - Pinedo, Gorka; Suárez-Lledó, María; Antonio, Maite; Guardia, Laia; Solé, Berta; Charry, Paola; Cid, Joan; Lozano, Miquel; Pedraza, Alejandra; Esteve, Jordi; Carreras, Enric; Fernández-Avilés, Francesc; et al. (Frontiers in Immunology, 2026)
IntroductionGiven the increasing number of older patients undergoing allo-HCT with post-transplant cyclophosphamide (PTCy)-based prophylaxis, a dedicated evaluation of its safety in this population is warranted.MethodsWe retrospectively analyzed 353 consecutive patients who underwent first allo-HCT with PTCy between 2014 and 2024. Patients were stratified into three age groups: ≤40 (24.4%), 41–64 (51.8%), and ≥65 (23.8%).ResultsMedian age was 53 years (range 18–75). Older patients mostly received RIC regimens and matched unrelated donors and younger MAC and haplo-HCT. Neutrophil and platelet engraftment occurred at amedian of 18 and 17 days, without differences among age groups. The incidence of grade II-IV aGVHD at day +100 was 22.4% with no differences according to age ranges (Day +100: 16.3%, 24.0% and 25.0%, P = 0.246) and moderate-severe cGVHD in 7.4%, with incidence significantly lower in patients ≥65 years (2-year: 3.1% vs. 12.1% and 4.8%; P = 0.023). At 2-years, OS rates were 79.5% for ≤40, 73.9% for 41–64, and 57.9% for ≥65 years (P = 0.001). NRM rates were 7.1%, 15.6%, and 16.0% (P = 0.128), and relapse incidence rates were, respectively, 26.2%, 24.6% and 40.7% (P = 0.039).DiscussionDespite higher relapse rates leading to lower OS in older adults, similar NRM and comparable early toxicities support the feasibility of allo-HCT with PTCy in patients ≥65 years.